2018
DOI: 10.1002/jcb.28036
|View full text |Cite
|
Sign up to set email alerts
|

Peptide selected by phage display increases survival of SH‐SY5Y neurons comparable to brain‐derived neurotrophic factor

Abstract: Brain‐derived neurotrophic factor (BDNF) is a well‐known neuroprotectant and a potent therapeutic candidate for neurodegenerative diseases. However, there are several clinical concerns about its therapeutic applications. In the current study, we designed and developed BDNF‐mimicking small peptides as an alternative to circumvent these problems. A phage‐displayed peptide library was screened using BDNF receptor (neurotrophic tyrosine kinase receptor type2 [NTRK2]) and evaluated by ELISA. The peptide sequences s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…RNYK also indicated neuroprotective activities at an optimum concentration of 5 ng/ml compared with BDNF at 50 ng/ml. This observation is in agreement with our previous studies showing that RNYK could prevent neuronal degeneration of ATRA-treated SH-SY5Y with equal efficacy to or even better than BDNF (Nafian, Rasaee, Yazdani, Daftarian, et al, 2018;.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…RNYK also indicated neuroprotective activities at an optimum concentration of 5 ng/ml compared with BDNF at 50 ng/ml. This observation is in agreement with our previous studies showing that RNYK could prevent neuronal degeneration of ATRA-treated SH-SY5Y with equal efficacy to or even better than BDNF (Nafian, Rasaee, Yazdani, Daftarian, et al, 2018;.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, at high doses and in long‐term delivery, BDNF may not increase cell survival or reverse neurodegeneration. Recently, we have demonstrated that RNYK as a novel BDNF mimetic can be an alternative to circumvent these problems (Nafian, Rasaee, Yazdani, Daftarian, et al, 2018; Nafian, Rasaee, Yazdani, & Soheili, 2018). RNYK has been selected from a phage‐displayed random peptide library with high‐affinity binding to NTRK2 and neurotrophic activities.…”
Section: Introductionmentioning
confidence: 99%
“…This previously confirmed that RNYK can mimic BDNF activities in vitro at an optimum concentration of 5 ng ml −1 . RNYK prevented neuronal degeneration of ATRA-treated SH-SY5Y with equal efficacy to or even better than BDNF at 50 ng ml −1 (Nafian et al, 2018). In the current study, RNYK indicated a neuroprotective effect comparable to BDNF on primary RGCs under both normal and elevated pressures.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this aim, we designed pressure chips in which HP could be modulated with the added benefits of higher speed, greater precision and finer control than previous EHP systems. We studied RGC survival under normal versus elevated hydrostatic pressures and also compared survival of these cells when treated with a neuroprotective growth factor (brain-derived neurotrophic factor, BDNF) or a mimicry peptide, named RNYK, as a putative agonist of neurotrophic tyrosine kinase receptor type 2 (NTRK2) (Nafian et al, 2018). BDNF is a well-known neuroprotectant and a potent therapeutic candidate for neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma‐on‐a‐chip provided an optimized glaucomatous condition, when subjected to a physiological microenvironment for proper communication of RGCs. [ 80 ]…”
Section: Organ‐on‐chip Models For Degenerative Diseasesmentioning
confidence: 99%